(untitled) (International Journal of Environmental Sciences, 2025)
Musculoskeletal injuries (MSIs) have emerged as a critical occupational health issue among endoscopy practitioners due to the physically demanding nature of their work. This cross-sectional study investigates the prevalence of MSIs and evaluates their impact on clinical practice. A structured questionnaire was distributed among gastroenterologists, colorectal surgeons, and other specialists involved in endoscopy to assess the frequency, location, severity, and clinical consequences of MSIs. Findings revealed a high prevalence of MSI, particularly affecting the neck, lower back, shoulders, and wrists. Many practitioners reported decreased work efficiency, procedural delays, and modified practices to accommodate symptoms. The study underscores the urgent need for ergonomic interventions and workload management to ensure practitioner well-being and sustained clinical performance.